Mental Health Survey of Social Entrepreneurs During COVID-19: A Study From Pakistan - Hussain, Nida; Li, Baoming (Frontiers in Psychiatry, 2022)
Background: COVID-19 is widely considered one of the worst pandemics in history, resulting in worldwide lockdowns, social isolation, unemployment, and economic recession. With the prolongation of COVID-19, numerous people experiencing stress, depression, and other mental health challenges. Recently, several studies have been documented in the literature on mental health issues among students (related to medical or other fields), teachers, medical personnel, and nurses in the wake of the COVID-19 pandemic. However, social entrepreneurs (SEs) have received insufficient attention. This study aims to conduct an online survey in Pakistan’s five major cities to investigate more about the mental health status of social entrepreneurs. Materials and Methods: An online survey which included the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) was employed to collect data. The data analyses were carried out employing descriptive statistics, chi-square test, and multiple regression analyses. Results: A total of 840 social entrepreneurs from Pakistan participated in the survey. Among these 366 (43.6%) were female and 474 (56.4%) were male. The findings revealed that 709 (84%) social entrepreneurs were suffering from depression symptoms, and 600 (80%) were suffering from anxiety symptoms. The majority of social entrepreneurs with depression (N=546) and anxiety (N=567) had mild and moderate stages. In addition, optional open-ended questions were asked from SE participants that help to understand their perception and response to the COVID-19 pandemic. Conclusion: The study concluded that several SEs in major cities of Pakistan were experiencing depression and anxiety symptoms. Based on data analysis, male SEs were highly suffering from depression and anxiety than female SEs. Limited resources and changes in customers' behaviour were one of the major problems that lead SEs to depression and anxiety during the COVID-19 epidemic. In addition, SEs revealed that the lack of a social business execution policy is the most distressing factor for them. Therefore, a local government must take rigorous precautionary measures to prevent mental health issues among social entrepreneurs. Moreover, the Government of Pakistan needs to adopt supportive policies to assist social entrepreneurs in stressful circumstances.